Levantamiento de procesos en el área de bodega de la empresa importadora Alvarado - Garcia Gavilanes, Kevin Geovanny (2024)
Importadora Alvarado CÍA. LTDA., is a company dedicated to the import and marketing of auto parts, with a wide variety of alternative and original products, with national coverage, personalized customer service and a highly qualified human staff. The company is located in Tungurahua province, specifically in the industrial sector of Ambato city. The problem focused on this information project is the insufficient and outdated information on its processes and procedures. To address this problem, direct observation techniques were used to collect information such as: process mapping for the preparation of flowcharts, coursegram, path diagrams, and online surveys for the analysis of the current situation of the company. A scope was defined that ranges from the collection of information to the proposal of a procedures manual. Through this research project, both processes and procedures were identified and whether the information contained in the proposal for a procedures manual was implemented. The results obtained were the lifting of a macroprocess, 5 processes, 12 procedures and 129 activities. Those ones constitute the processes of reception, dispatch, system change and inventories, which represent the general vision of the Warehouse Area. Whitin the results, there is the developed and proposed procedures manual, which provides detailed information of identified activities. Process lifting is an essential tool to achieve significant improvements in the company.